KEDUDUKAN DAN FUNGSI HADITS DALAM ISLAM - Rizka, Alviana (Jurnal Pendidikan Agama Islam, 2025)
Hadith is one of the foundational sources in the Islamic legal system, ranking second after the Qur'an. This study aims to comprehensively analyze the status and function of hadith within the framework of Islamic law, education, and the daily life of Muslims. Employing a qualitative-descriptive approach, this paper explores the definitions of hadith from various scholarly perspectives, its historical transmission and codification, as well as its role in Uṣūl al-Fiqh as a tool for legal reasoning (istinbāṭ al-ḥukm). The findings reveal that hadith serves a strategic function as an explanatory (bayān), confirmatory (taqrīr), legislative (tashrīʿ), and even abrogating (naskh) source, in addition to its essential role in the development of Islamic ethics and character. Therefore, a deep understanding of hadith is indispensable for preserving the integrity of Islamic teachings and addressing contemporary socio-religious dynamics. This study recommends the advancement of hadith studies methodologies that are responsive to the progression of scientific disciplines and the evolving needs of the Muslim community.